Review of 5Gmobile communication technology standard - Ying DU; Hao ZHU; Hongmei YANG; Zhiqin WANG; Yang XU (Dianxin kexue)
The industry is working togetheRto create 5G technology standard,which shouldmeet the needs ofmobile broadband and internet of things.Recently,3GPP declares the first 5G standard which supports the standalone deployment frozen.5G supports wider bandwidth,low latency,flexible configuration.New service-based architecture is designed for 5G,which supports important service capabilities,e.g.network slice,edge computing.5G standards were introduced,including new radio,new core and security.In the end,the trends of 5G standard were summarized.